2010
DOI: 10.1159/000276665
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium in Chronic Kidney Disease: Challenges and Opportunities

Abstract: Cardiovascular disease is the leading cause of mortality and morbidity in patients with chronic kidney disease, which is partly explained by the fact that 40–70% of patients receiving dialysis have significant coronary artery disease. Recent clinical studies have shown that lower serum magnesium (Mg) levels are associated with vascular calcification and cardiovascular mortality among patients with end-stage renal disease (ESRD). On the other hand, hypermagnesemia inhibits parathyroid hormone secretion, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(61 citation statements)
references
References 92 publications
1
58
0
1
Order By: Relevance
“…20,21 However, compared to the wide attention in the derangement of calcium/phosphate metabolism and the vascular/valvular calcification, the magnesium metabolism is usually neglected and is still among the less well understood clinical problems encountered by nephrologists until now. 22,23 Recently, since numerous studies suggested an association between hypomagnesaemia and risk factors of cardiovascular disease, such as diabetes mellitus, metabolic syndrome, coronary artery disease and atherosclerosis risk in the general population, 24,25 the impact of magnesium disorders on the prognosis of patients with chronic kidney disease has received a great deal of interest. Although clinical and epidemiological studies have consistently suggested that lower serum magnesium levels were associated with vascular calcification and cardiovascular mortality among patients with end-stage renal disease (ESRD), 19,[26][27][28] the pathophysiology and the role of magnesium disturbances in chronic kidney disease still need further studies.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 However, compared to the wide attention in the derangement of calcium/phosphate metabolism and the vascular/valvular calcification, the magnesium metabolism is usually neglected and is still among the less well understood clinical problems encountered by nephrologists until now. 22,23 Recently, since numerous studies suggested an association between hypomagnesaemia and risk factors of cardiovascular disease, such as diabetes mellitus, metabolic syndrome, coronary artery disease and atherosclerosis risk in the general population, 24,25 the impact of magnesium disorders on the prognosis of patients with chronic kidney disease has received a great deal of interest. Although clinical and epidemiological studies have consistently suggested that lower serum magnesium levels were associated with vascular calcification and cardiovascular mortality among patients with end-stage renal disease (ESRD), 19,[26][27][28] the pathophysiology and the role of magnesium disturbances in chronic kidney disease still need further studies.…”
Section: Discussionmentioning
confidence: 99%
“…З огляду на підвищений ризик серцево-судинної патології у пацієнтів із хронічною хворобою нирок, гіпомагніємія потребує особливої уваги у цією когорти пацієнтів, оскільки магній сповільнює розвиток кальцифікації судин, також запобігає розвитку аритмій, регулює артеріальний тиск шляхом зменшення загального периферично-го опору, виявляє антитромботичну дію, стимулює синтез оксиду азоту, зменшує запальну відповідь та полегшує реендотеліалізацію судинних пошко-джень [7].…”
Section: рисунокunclassified
“…However, in another study of 11,500 patients from the Dialysis Outcomes and Practice Patterns Study (DOPPS), Hecking et al found the prevalence of mean pre-dialysis serum sodium level lower than 137 mmol/L to be 27% and that of mean pre-dialysis serum sodium level higher than or equals to 140 mmol/L to be 31% [6]. Hyponatremia is a frequently seen electrolyte disorder while hypermagnesemia is also highly prevalent in MHD patients and it tends to be in a higher percentage than hypomagnesemia [7] [8] [9] [10]. In a cohort study of 27,544 MHD patients in the United States, 4729 patients (17.2%) had hypomagnesemia and 6133 patients (22.3%) had hypermagnesemia [10].…”
Section: Prevalence Of Serum Electrolytes Abnormalitiesmentioning
confidence: 99%